2020
DOI: 10.1002/fsn3.1928
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics on the oxidation stability of infant formula powder with different ingredients during storage

Abstract: Milk powder is a favorite food for consumers. However, milk powder is prone to lipid oxidation during processing and storage. Free radicals are produced in the induction stage of lipid oxidation. Then hydroperoxides are formed from free radicals by reaction with oxygen (Hong et al., 2017). That will automatically form chain reaction and promote some related reactions, leading to the decline of milk powder quality (Cluskey et al., 2006; Concetta et al., 2020; Nursten, 1997). The oxidation deterioration during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Of the RTF that were tested, enriched infant formula had the highest amount of PV on the purchase date but did not change significantly after 3-month storage. Previous studies have also demonstrated that omega 3-enriched infant formulas contain higher amounts of lipid hydroperoxides and MDA as compared to un-enriched infant formula [28]. The levels of lipid oxidation products in French fries and chicken nuggets were similar to those in the RTF and not higher as we originally hypothesized.…”
Section: Discussionsupporting
confidence: 65%
“…Of the RTF that were tested, enriched infant formula had the highest amount of PV on the purchase date but did not change significantly after 3-month storage. Previous studies have also demonstrated that omega 3-enriched infant formulas contain higher amounts of lipid hydroperoxides and MDA as compared to un-enriched infant formula [28]. The levels of lipid oxidation products in French fries and chicken nuggets were similar to those in the RTF and not higher as we originally hypothesized.…”
Section: Discussionsupporting
confidence: 65%
“…Secondary lipid oxidation products, such as aldehydes and ketones, impact the sensory characteristics of lipids-containing dairy powders [ 65 ]. Hexanal is a major product of linoleic acid oxidation; it is involved in the evolution of oxidized flavor in dairy powders and its accumulation has thus been used as an indicator for the oxidative state of the powder [ 36 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hexanal accumulation during storage is affected by the combined influence of different variables such as storage temperature, fatty acids composition, packaging aspects, presence of metal ions, presence of antioxidants, etc. [ 65 , 67 ]. The odor thresholds of hexanal varies as a function of the medium or matrix in which it is included and it ranges from 0.012 mg/kg in water to 0.32 or 0.075 mg/kg in oil, depending on the sensing mode [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 49 reported the change in surface fat during storage of commercial infant formulas and found that the surface free fat reached 8.71 g/100 g after 9 months of storage in one of the formulas. Wang et al 55 also demonstrated that surface fat increased to 3.62 g/100 g after 6 months in storage of milk powder. Although the samples of this batches had been stored for 2 years so far, the EEs of all milk powder groups were more than 60%.…”
Section: The Stability Of Milk Powdermentioning
confidence: 94%